Neo-Kaleckian and neo-Marxian regime research: A promising scientific research programme or a scientific cul-de-sac? - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2019)
[Introduction] Over the past three decades, a small but very productive Post-Keynesian and Marxian research community has engaged in the elaboration of a scientific research programme (SRP) that has come to be known as wage and profit-led regime research.1 In dozens of journal articles in almost every heterodox economic journal, particularly the Cambridge Journal of Economics, the primary aim has been to reiterate the classical political economy conception of functional income distribution as a major determinant of economic development and employment, from both a Keynesian (effective demand) and Marxian (class struggle) perspective. Only recently, the Review of Keynesian Economics (RoKE) dedicated - convening almost the entire 'wage and profit-led regime' community - an incredible four (consecutive) issues to delineating and discussing this Denkstil. The International Labour Office (ILO), meanwhile, commissioned a major research initiative investigating the relationship between functional income distribution and growth (see Lavoie/Stockhammer 2013a).2 Since only very few critical voices (such as Peter Skott (2017) joined this illustrious debate, I would like to re-open this discussion about the scientific and political merits of the 'wage and profit-led regime' approach. My intention is to examine whether this SRP can fill an obvious gap in Post-Keynesian theory. In accordance with Keynes' considerable neglect of distributional questions in his General Theory, most Post-Keynesians have underemphasised a phenomenon that has become one of the most socially and politically concerning problems of our times: growing income inequality. This article is structured as follows: in the next section, the main arguments of the wage and profit-led regime approach will be delineated and scrutinised with reference to the Bhaduri-Marglin model, which is regarded as 'a widely used workhorse model' (Stockhammer 2017: 25). I will subsequently question its theoretical bases, its empirical validity, and its policy applicability. Finally, I offer a number of concluding remarks on the merits of the distributional regime approach.
Keywords: 330